(untitled) (Global Journal of Human-Social Science, 2023)
The unprecedented number of working mothers pursuing master s education this year is captivating This reality triggered a closer look to scrutinize underlying motives behind this undertaking A mixed-method was used to capture the incentives for the satisfactory educational results achieved by this category of students Five older learners out of twentyfive enrolling in a master s degree at Dr Tahar Moulay University of Saida Algeria are the focus of this study The prominence was in favor of adults rather than youngsters The findings postulate that the following dual consideration is worth pointing out the extrinsic reward motivation which surfaces besides brain maturation appears of paramount importance in academic engagement